2017
DOI: 10.1039/c6sm02374f
|View full text |Cite
|
Sign up to set email alerts
|

Outflow and clogging of shape-anisotropic grains in hoppers with small apertures

Abstract: Outflow of granular material through a small orifice is a fundamental process in many industrial fields, for example in silo discharge, and in everyday's life. Most experimental studies of the dynamics have been performed so far with monodisperse disks in two-dimensional (2D) hoppers or spherical grains in 3D. We investigate this process for shape-anisotropic grains in 3D hoppers and discuss the role of size and shape parameters on avalanche statistics, clogging states, and mean flow velocities. It is shown th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 67 publications
6
64
0
1
Order By: Relevance
“…For hard spheres, Thomas et al [12] have shown that Beverloo's equation fits the continuous flow of hard particles at high opening sizes as well as the flow within avalanches through narrow openings, and that there is no discontinuity in the dynamic parameters. This was confirmed in our earlier experiments with non-spherical hard grains [19]. For the soft spheres, the validity of Beverloo's equation cannot be tested in the limit of small orifice sizes.…”
Section: Figsupporting
confidence: 65%
See 1 more Smart Citation
“…For hard spheres, Thomas et al [12] have shown that Beverloo's equation fits the continuous flow of hard particles at high opening sizes as well as the flow within avalanches through narrow openings, and that there is no discontinuity in the dynamic parameters. This was confirmed in our earlier experiments with non-spherical hard grains [19]. For the soft spheres, the validity of Beverloo's equation cannot be tested in the limit of small orifice sizes.…”
Section: Figsupporting
confidence: 65%
“…Even small modifications of these features can have dramatic qualitative consequences [19]. However, studies of elastic particles, for example, are rather scarce.…”
mentioning
confidence: 99%
“…In some experiments with the hard ASB, the system produced clogs. In those cases, flow was restarted by a manually triggered airflush into the orifice [7].…”
Section: Experimental Setup and Materialsmentioning
confidence: 99%
“…When the particles are soft and slippery, they flow through much narrower outlets without clogging [3][4][5]. For non-spherical particles, shape parameters influence the discharge statistics [6,7]. Despite the high practical importance of this process in agriculture, building industry, pharmacy and many other fields where grains are stored and processed, our understanding of the discharge of grains through narrow orifices is still quite incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…The placement of an obstacle above the orifice can prevent clogging if its position is appropriately selected [6]. Other variables that have been shown to affect clogging are orifice geometry [16,17], particle shape [18][19][20], particle polydispersity [21], and gravity [22][23][24]. Nevertheless, we are not aware of any work looking at the influence of the width of the silo, a variable that in most of the existing experiments and simulations remains uncontrolled.…”
Section: Introductionmentioning
confidence: 98%